MUSIK ETNIK DAN PENGEMBANGAN MUSIK GEREJA - Michael Hari Sasongko (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2019)
Church, as a religious institution, and ethnic music, as a communality creation, are different thing. They have different philosophy, meaning, existence, entity, form, and also sosial and historical context. Sometimes even as, ideologically, they display even negation. However inspite of the contradiction, they have some interest and orientation i.e. come together on a place for expressing who people are. When they meet, there, they create something new. Based on Homi K. bhabha's theory, this something new is called "the third space". We will find ambivalence and mimicry in the new space. On the musical perspective, the hybrid of church and ethnic music call into being a new genre, namely "ethnical church music". The cutting-edge genre proved succeed for increasing worship atmosphere.